PERILAKU SEHAT PENDERITA KUSTA DENGAN KEPATUHAN KONSUMSI MDT DI PUSKESMAS LIMO KOTA DEPOK JAWA BARAT - Siregar, Tatiana; Ratnawati, Diah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2019)
Leprosy is a disease caused by the bacterium Mycobacterium leprae, will attack the skin and peripheral nerves, and is transmitted through the upper respiratory tract. Management of leprosy requires patient patience in treatment, because it takes a long time. Patient compliance in the treatment process determines the success of treatment. Healthy behavior in the management of leprosy treatment requires discipline in taking leprosy medication. Poor treatment management can have permanent damage to the limbs of the patient, which is the occurrence of disability. The purpose of this study was to determine the main factor dimensions of healthy behavior that affect leprosy compliance in consuming Multi Drug Therafi (MDT) of leprosy. The research design used cross sectional descriptive, the sampling technique used was a total sampling of 15 people. The research instrument used a questionnaire containing statements of compliance and healthy behavior consisting of dimensions of knowledge, attitudes and psychomotor, and analyzed using multiple linear regression. The results obtained that the factors of knowledge, attitudes, and psychomotor have a positive and significant effect on patient compliance consuming MDT (p value